Factors related to on-treatment platelet aggregation assessed by multiple electrode aggregometry in percutaneous coronary intervention patients on clopidogrel and aspirin - Kukula, Krzysztof; Klopotowski, Mariusz; Was, Joanna; Wrobel, Aleksandra; Jamiolkowski, Jacek; Debski, Artur; Bekta, Pawel; Chmielak, Zbigniew; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : There is ongoing controversy concerning the clinical value of platelet function monitoring in patients undergoing percutaneous coronary interventions (PCI). Patients at risk of high on-treatment platelet aggregation (HPR) may benefit most from such monitoring. Aim : To define the factors related to HPR on aspirin and clopidogrel, looking at a wider spectrum of variables than those assessed in some previous studies. Material and methods: We assessed platelet function in 908 patients on clopidogrel and aspirin after PCI using the multielectrode aggregometry system Multiplate to define which clinical, procedural and laboratory factors are related to on-treatment platelet aggregation in response to aspirin and clopidogrel either as linear values or using established cutoff values for HPR. Results : We found that in PCI patients on clopidogrel and aspirin, age (OR per year 1.06; 95% CI: 1.024–1.097; p = 0.001), gender (OR = 0.319; 95% CI: 0.139–0.731; p = 0.007), active smoking (OR = 2.57; 95% CI: 1.29–5.15; p = 0.008), diabetes ( = 37.6; 95% CI: 16.5–58.8; p = 0.001) and hypertension ( = 26.9; 95% CI: 6.73–47.1; p = 0.009) are independently linked to platelet aggregation values treated as linear values and as dichotomous variables at the accepted cutoffs. The same is true for stented segment length (OR per mm 1.033; 95% CI: 1.010–1.057; p = 0.009) and stent inflation pressure (OR per atmosphere 0.862; 95% CI: 0.772–0.963; p = 0.002). Conclusions : The study shows that, contrary to some earlier data, in the tested cohort women are better clopidogrel responders, but more often aspirin low-responders. Older age, active smoking, diabetes and hypertension all predispose to HPR. A novel finding is that stented segment length is an independent predictor of lower response both to aspirin and clopidogrel, possibly as a marker of more diffuse atherosclerosis.